Developmental Profile of Ion Channel Specializations in the Avian Nucleus Magnocellularis - Hong, Hui; Rollman, Lisia; Feinstein, Brooke; Sanchez, Jason Tait (Frontiers in Cellular Neuroscience, 2016)
Ultrafast and temporally precise action potentials (APs) are biophysical specializations of auditory brainstem neurons; properties necessary for encoding sound localization and communication cues. Fundamental to these specializations are voltage dependent potassium (KV) and sodium (NaV) ion channels. Here we characterized the functional development of these ion channels and quantified how they shape AP properties in the avian cochlear nucleus magnocellularis (NM). We report that late developing NM neurons (embryonic [E] days 19-21) generate fast APs that reliably phase lock to sinusoidal inputs at 75 Hz. In contrast, early developing neurons (<E12) have slower and less reliable APs that preferentially fire to lower frequencies (5-10 Hz). With development, the membrane time constant of NM neurons became faster, while input resistance and capacitance decreased. Change in input resistance was due to a 2-fold increase in KV current from E10 to E21 and when high-voltage activated potassium (K+HVA) channels were blocked, APs for all ages became significantly slower. This was most evident for early developing neurons where the ratio of K+HVA current accounted for 85% of the total KV response. This ratio dropped to 50% for late developing neurons, suggesting a developmental upregulation of low-voltage activated potassium (K+LVA) channels. Indeed, blockade of K+LVA eliminated remaining current and increased neural excitability for late developing neurons. We also report developmental changes in the amplitude, kinetics and voltage dependence of NaV currents. For early developing neurons, increase in NaV current amplitude was due to channel density while channel conductance dominated for late developing neurons. From E10 to E21, NaV channel currents became faster but differed in their voltage dependence; early developing neurons (<E16) had similar NaV channel inactivation voltages while late developing NM neurons (>E19) contained NaV channels that inactivate at more negative voltages, suggesting alterations in NaV channel subtypes. Taken together, our results indicate that the refinement of passive and active ion channel properties operate differentially in order to develop fast and reliable APs in the avian NM.